The Application of Simple Additive Weighting Method in the Selection of the Islamic Competition Winners (Journal of Advances in Information Systems and Technology, 2019)
The IRMA Islamic Competition is an Islamic contest held by mosque youth association (IRMA) of the Baitul Muttaqien Mosque at Dolog Housing. Currently, the calculation and ranking method is still conducted manually, and it takes a long time. The data recording process also still using a paper which at any time the recorded data can be damaged or lost before the announcement of the winners of the competition. This study aims to build a decision support system for the selection of the winners of the IRMA Islamic Competition. The simple additive weighting (SAW) method was used to be implemented in the system. The results of the study show that the use of the SAW method effectively helps the committee to easily determine the winners of the competition.